Comparative efficacy of non-pharmacological management for chronic prostatitis/chronic pelvic pain syndrome: a systematic review and network meta-analysis protocol - Chao Zhang; Joey S W Kwong; Jiani Wu; Zongshi Qin; Yanlan Yu; Xinyao Wei; Jiaming Cui; Ran Pang; R. Christopher Doiron; J. Curtis Nickel (BMJ Open)
Background Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) has posed a significant burden on affected individuals and healthcare systems. While pharmacological treatments are commonly used, non-pharmacological management strategies have gained attention for their potential benefits in improving CP/CPPS symptoms. However, the comparative efficacy of these non-pharmacological interventions remains unclear. The aim of this study is to assess the comparative effectiveness of non-pharmacological interventions for CP/CPPS regarding prostatic symptoms.Method This systematic review and network meta-analysis will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A comprehensive search will be conducted in electronic databases, including PubMed, Embase, Cochrane Library and Web of Science, to identify relevant studies. Eligible studies will include randomised controlled trials investigating non-pharmacological management strategies for CP/CPPS. Two independent reviewers will screen the retrieved citations, extract data and assess the risk of bias. Data synthesis will involve performing a network meta-analysis to compare the efficacy of different non-pharmacological interventions while considering both direct and indirect evidence.Ethics and dissemination The review does not require ethical approval. The findings of the review will be disseminated through publication in an academic journal, presentations at conferences and various media outlets.PROSPERO registration number CRD42024506143.